A Proposal for Green Financing as a Mechanism to Increase Private Participation in Sustainable Water Infrastructure Systems: The Colombian Case. (2016) - Ruiz, J.D. González; Arboleda, C.A.; Botero, S.
Abstract: Many countries, including Colombia, require new financial mechanisms that lead to increased coverage in supplies of drinking water, particularly in rural areas. However, the establishment of such mechanisms demands new public and private policies that promote and increase financial assets in capital markets. This paper examines how green financial mechanisms can lead to increased coverage of potable water through the funding of new water infrastructure systems in Colombia. Achieving this goal requires both private investment and clean financial mechanisms that promote a low-emissions infrastructure. To address this need, this paper proposes a new financing model that involves green financing, capital markets, and the private and public sectors. In addition, it introduces new policies that the Colombian government should plan to implement to foster private participation and the development of infrastructure-related financial assets. As a result, this paper should contribute to increasing the role of the capital markets and private involvement in the development of a sustainable rural drinking water infrastructure.